HUBUNGAN TINGKAT EKONOMI DENGAN MOTIVASI ORANG TUA MEMASUKAN ANAKNYA KE LEMBAGA PAUD DI NAGARI AMPING PARAK TIMUR KECAMATAN SUTERA PESISIR SELATAN - Isma wati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
This study started from the low motivation of parents to enter their children into PAUD Institute. The hypothesis of this study that there is a relationship between the level of economic with the motivation of parents to enter their children into PAUD Institute. The purpose of this study is to describe the correlation between parents' economic and motivation of parents to send their children to PAUD Institute. The results of the research is that almost all respondents have low parents' economic level, there is a significant relationship between the parents’ economic level with the motivation of parents to enter their children into PAUD.